YES(?,O(n^2)) Problem: f(0()) -> s(0()) f(s(x)) -> g(s(s(x))) g(0()) -> s(0()) g(s(0())) -> s(0()) g(s(s(x))) -> f(x) Proof: Complexity Transformation Processor: strict: f(0()) -> s(0()) f(s(x)) -> g(s(s(x))) g(0()) -> s(0()) g(s(0())) -> s(0()) g(s(s(x))) -> f(x) weak: Matrix Interpretation Processor: dimension: 1 max_matrix: 1 interpretation: [g](x0) = x0, [s](x0) = x0 + 1, [f](x0) = x0, [0] = 1 orientation: f(0()) = 1 >= 2 = s(0()) f(s(x)) = x + 1 >= x + 2 = g(s(s(x))) g(0()) = 1 >= 2 = s(0()) g(s(0())) = 2 >= 2 = s(0()) g(s(s(x))) = x + 2 >= x = f(x) problem: strict: f(0()) -> s(0()) f(s(x)) -> g(s(s(x))) g(0()) -> s(0()) g(s(0())) -> s(0()) weak: g(s(s(x))) -> f(x) Matrix Interpretation Processor: dimension: 1 max_matrix: 1 interpretation: [g](x0) = x0 + 1, [s](x0) = x0, [f](x0) = x0, [0] = 0 orientation: f(0()) = 0 >= 0 = s(0()) f(s(x)) = x >= x + 1 = g(s(s(x))) g(0()) = 1 >= 0 = s(0()) g(s(0())) = 1 >= 0 = s(0()) g(s(s(x))) = x + 1 >= x = f(x) problem: strict: f(0()) -> s(0()) f(s(x)) -> g(s(s(x))) weak: g(0()) -> s(0()) g(s(0())) -> s(0()) g(s(s(x))) -> f(x) Matrix Interpretation Processor: dimension: 1 max_matrix: 1 interpretation: [g](x0) = x0 + 1, [s](x0) = x0, [f](x0) = x0 + 1, [0] = 0 orientation: f(0()) = 1 >= 0 = s(0()) f(s(x)) = x + 1 >= x + 1 = g(s(s(x))) g(0()) = 1 >= 0 = s(0()) g(s(0())) = 1 >= 0 = s(0()) g(s(s(x))) = x + 1 >= x + 1 = f(x) problem: strict: f(s(x)) -> g(s(s(x))) weak: f(0()) -> s(0()) g(0()) -> s(0()) g(s(0())) -> s(0()) g(s(s(x))) -> f(x) Matrix Interpretation Processor: dimension: 2 max_matrix: [1 1] [0 1] interpretation: [1 0] [0] [g](x0) = [0 0]x0 + [1], [1 1] [0] [s](x0) = [0 1]x0 + [1], [1 1] [1] [f](x0) = [0 0]x0 + [1], [1] [0] = [0] orientation: [1 2] [2] [1 2] [1] f(s(x)) = [0 0]x + [1] >= [0 0]x + [1] = g(s(s(x))) [2] [1] f(0()) = [1] >= [1] = s(0()) [1] [1] g(0()) = [1] >= [1] = s(0()) [1] [1] g(s(0())) = [1] >= [1] = s(0()) [1 2] [1] [1 1] [1] g(s(s(x))) = [0 0]x + [1] >= [0 0]x + [1] = f(x) problem: strict: weak: f(s(x)) -> g(s(s(x))) f(0()) -> s(0()) g(0()) -> s(0()) g(s(0())) -> s(0()) g(s(s(x))) -> f(x) Qed